Nucleic Acid Testing for Diagnosis of Perinatally Acquired Hepatitis C Virus Infection in Early Infancy. (8th July 2020) - Gowda, Charitha; Smith, Stephanie; Crim, Linda; Moyer, Katherine; Sánchez, Pablo J; Honegger, Jonathan R
Abstract: Background: Most US children with perinatal hepatitis C virus (HCV) exposure fail to receive the recommended anti-HCV antibody test at age ≥18 months. Earlier testing for viral RNA might facilitate increased screening, but sensitivity of this approach has not been established. We hypothesized that modern HCV-RNA RT-PCR platforms would adequately detect infected infants. Methods: Nationwide Children's Hospital electronic health records from 1/1/2008 to 30/6/2018 were reviewed to identify perinatally exposed infants tested by HCV-RNA RT-PCR at age 2–6 months. Diagnostic performance was determined using a composite case definition: (1) infected children had positive repeat HCV-RNA testing or positive anti-HCV at age ≥24 months; (2) uninfected children lacked these criteria and had negative anti-HCV at age ≥18 months. Results: 770 perinatally exposed infants underwent HCV-RNA testing at age 2–6 months. Of these, 28 (3.6%) tested positive; viremia was confirmed in all who underwent repeat testing (n = 27). Among 742 infants with negative HCV-RNA results, 226 received follow-up anti-HCV testing at age ≥18 months, of whom 223 tested negative. Three children had low-positive anti-HCV results at age 18–24 months that were negative upon retesting after age 24 months, possibly indicating waning maternal antibodies. Using the composite case definitions, early HCV-RNA screening demonstrated sensitivity of 100% (87.5–100%, Wilson-Brown 95% CI) and specificity of 100% (98.3–100%). Conclusions: Modern HCV-RNA RT-PCR assays have excellent sensitivity for early diagnosis of perinatally acquired infection and could aid HCV surveillance given the substantial loss to follow-up at ≥18 months of age. Abstract : Hepatitis C virus (HCV)-RNA testing during infancy could improve screening rates for children born to infected mothers, but diagnostic sensitivity is not established. We found excellent sensitivity of HCV-RNA reverse transcription–polymerase chain reaction performed at age 2–6 months for detection of perinatally acquired infection.